An open-label, single-dose, phase 1 study of the absorption, metabolism and excretion of quizartinib, a highly selective and potent FLT3 tyrosine kinase inhibitor, in healthy male subjects, for the treatment of acute myeloid leukemia*. (3rd October 2017) - Sanga, Madhu; James, Joyce; Marini, Joseph; Gammon, Guy; Hale, Christine; Li, Jianke
Abstract: 1. Quizartinib absorption, metabolism and excretion were characterized in six healthy men receiving a single oral dose of 60 mg (≈100 μCi) of [ 14 C]-quizartinib. Blood, plasma, urine and faeces were collected ≤336 h postdose. 2. Four hours postdose, maximum mean ± SD blood radioactivity concentrations were 296 ± 67.4 ng equivalents/g. A mean ± SD of 1.64 ± 0.482% and 76.3 ± 6.23% of the dose was recovered in urine and faeces, respectively, within 336 h postdose. 3. Radio-detector high-performance liquid chromatography (radio-HPLC) and liquid chromatography–mass spectrometry (LC–MS) showed two main radioactive peaks in plasma, unchanged quizartinib and mono-oxidative metabolite, AC886. Five additional metabolites in plasma were identified by LC–MS, but low levels prevented radio-HPLC detection. Although unchanged quizartinib was the main radioactive component in faeces (mean, 4.0% of administered dose), 15 metabolites representing a mean of 1.0–3.5% of administered dose were found. Quizartinib was predominantly metabolized by phase I biotransformations (oxidation, reduction, dealkylation, deamination, hydrolysis and combinations thereof). 4. This study indicated that quizartinib was rapidly and orally bioavailable, extensively metabolized, with AC886 as the major circulating metabolite, and predominantly eliminated in faeces. Quizartinib was well tolerated in the subjects.